Shifting attitudes and the labor market of minorities: Swedish experiences after 9-11 - Olof Åslund; Dan-Olof Rooth (Institute for Labour Market Policy Evaluation (IFAU), 2004)
Several studies suggest that the terrorist attacks in the US on September 11, 2001, caused at least a temporary change of attitude toward certain minorities in Sweden. We study unemployment exit around 9-11 using detailed data on the entire Swedish working-age population to investigate whether this change in attitudes also affected the labor market situation of these minorities. Contrary to what to expect from many theories of labor market discrimination, the time pattern of exits and entries for different ethnic groups, as well as difference-in-differences analyses, show no sign of increased discrimination towards these minorities.
Keywords: J71; 330; Labour market discrimination; minorities; etnic groups